Targeted NGF siRNA delivery attenuates sympathetic nerve sprouting and deteriorates cardiac dysfunction in rats with myocardial infarction. - Hesheng Hu (Public Library of Science (PLoS), 2014)
Nerve growth factor (NGF) is involved in nerve sprouting, hyper-innervation, angiogenesis, anti-apoptosis, and preservation of cardiac function after myocardial infarction (MI). Positively modulating NGF expression may represent a novel pharmacological strategy to improve post-infarction prognosis. In this study, lentivirus encoding NGF short interfering RNA (siRNA) was prepared, and MI was modeled in the rat using left anterior descending coronary artery ligation. Rats were randomly grouped to receive intramyocardial injection of lentiviral solution containing NGF-siRNA (n = 19, MI-SiNGF group), lentiviral solution containing empty vector (n = 18, MI-GFP group) or 0.9% NaCl solution (n = 18, MI-control group), or to receive thoracotomy and pericardiotomy (n = 17, sham-operated group). At 1, 2, 4, and 8 wk after transduction, rats in the MI-control group had higher levels of NGF mRNA and protein than those in the sham-operated group, rats in the MI-GFP group showed similar levels as the MI-control group, and rats in the MI-SiNGF group had lower levels compared to the MI-GFP group, indicating that MI model was successfully established and NGF siRNA effectively inhibited the expression of NGF. At 8 wk, echocardiographic and hemodynamic studies revealed a more severe cardiac dysfunction in the MI-siRNA group compared to the MI-GFP group. Moreover, rats in the MI-siRNA group had lower mRNA and protein expression levels of tyrosine hydroxylase (TH) and growth-associated protein 43-positive nerve fibers (GAP-43) at both the infarcted border and within the non-infarcted left ventricles (LV). NGF silencing also reduced the vascular endothelial growth factor (VEGF) expression and decreased the arteriolar and capillary densities at the infarcted border compared to the MI-GFP group. Histological analysis indicated a large infarcted size in the MI-SiNGF group. These findings suggested that endogenous NGF silencing attenuated sympathetic nerve sprouting and angiogenesis, enlarged the infarct size, aggravated cardiac dysfunction, and potentially contributed to an unfavorable prognosis after MI.